Algunas consideraciones respecto de cláusulas típicas en contratos de M&A a la luz de las normas civiles peruana - Gonzáles La Rosa, Daniel (2020)
The sustained economic growth that Peru has experienced during the last two decades has caused the proliferation of acquisitions of companies, or M&A, in our country. The following article seeks to analyze an important figure in M&A contracts, the temporary limitations to the indemnification obligations, in light of the civil norms that apply to stock purchase agreements according to Peruvian legislation.